The geochemistry of naturally occurring methane and saline groundwater in an area of unconventional shale gas development. (1st July 2017) - Harkness, Jennifer S.; Darrah, Thomas H.; Warner, Nathaniel R.; Whyte, Colin J.; Moore, Myles T.; Millot, Romain; Kloppmann, Wolfram; Jackson, Robert B.; Vengosh, Avner
Abstract: Since naturally occurring methane and saline groundwater are nearly ubiquitous in many sedimentary basins, delineating the effects of anthropogenic contamination sources is a major challenge for evaluating the impact of unconventional shale gas development on water quality. This study investigates the geochemical variations of groundwater and surface water before, during, and after hydraulic fracturing and in relation to various geospatial parameters in an area of shale gas development in northwestern West Virginia, United States. To our knowledge, we are the first to report a broadly integrated study of various geochemical techniques designed to distinguish natural from anthropogenic sources of natural gas and salt contaminants both before and after drilling. These measurements include inorganic geochemistry (major cations and anions), stable isotopes of select inorganic constituents including strontium ( 87 Sr/ 86 Sr), boron (δ 11 B), lithium (δ 7 Li), and carbon (δ 13 C-DIC), select hydrocarbon molecular (methane, ethane, propane, butane, and pentane) and isotopic tracers (δ 13 C-CH4, δ 13 C-C2 H6 ), tritium ( 3 H), and noble gas elemental and isotopic composition (helium, neon, argon) in 105 drinking-water wells, with repeat testing in 33 of the wells (total samples = 145). In a subset of wells ( n = 20), we investigated the variations in water quality before and after the installation of nearby (<1 km) shale-gas wells. Methane occurred above 1 ccSTP/L in 37% of the groundwater samples and in 79% of the samples with elevated salinity (chloride > 50 mg/L). The integrated geochemical data indicate that the saline groundwater originated via naturally occurring processes, presumably from the migration of deeper methane-rich brines that have interacted extensively with coal lithologies. These observations were consistent with the lack of changes in water quality observed in drinking-water wells following the installation of nearby shale-gas wells. In contrast to groundwater samples that showed no evidence of anthropogenic contamination, the chemistry and isotope ratios of surface waters ( n = 8) near known spills or leaks occurring at disposal sites mimicked the composition of Marcellus flowback fluids, and show direct evidence for impact on surface water by fluids accidentally released from nearby shale-gas well pads and oil and gas wastewater disposal sites. Overall this study presents a comprehensive geochemical framework that can be used as a template for assessing the sources of elevated hydrocarbons and salts to water resources in areas potentially impacted by oil and gas development.